The Effect of Cognitive Rehabilitation on the Improvement of Language Skills in 9-12 Years Old Children with Attention Deficit/ Hyperactivity Disorder - Masoomeh Asef; Vahid Nejati; Masood Sharif (Journal of Rehabilitation Sciences and Research, 2017)
Background: According to the research literature, there was a relationship between cognitive functions of attention and working memory and linguistic skills. The aim of this research was to investigate the effect of cognitive rehabilitation on the improvement of the linguistic skills in 9-12 years old children with attention-deficit/hyperactivity disorder. Methods: 40 students in grade 4, 5 and 6 of a primary school in Miyane city were assigned equally and randomly to two intervention and control groups. The research design was experimental with pre-test, post-test, follow-up, and control group. The language tests included; Thurston Verbal Fluency task, Token test of receptive language, Boston naming speed test, Assessment of Persian Reading Ability (APRA), verbal working memory subtest of Wechsler Intelligence Scale for Children, and Attention Register task. Parental version of the Swanson, Nolan, and Pelham (SNAP-IV) questionnaire was used to screen ADHD. The intervention method was based on Attentive Rehabilitation of Attention and Memory (ARAM) with emphasis on attention and working memory. Mixed ANOVA statistical test was used to analyze the data. Results: The results showed that the linguistic skills assessed in the research which include naming (F=29.42, P=0.01), verbal fluency (phonological fluency: F=15.68, P=0.01; semantic fluency: F=13.73, P=0.01), reading abilities (alphabet reading 1: F=17.84, P=0.01; alphabet reading 2: F=27.07, P=0.01; word reading: F=19.82, P=0.01; reading ability: F=19.97, P=0.01; voice change: F=13.47, P=0.01; reading comprehension: F=36.85, P=0.01), comprehension (F=6.75, P=0.01), verbal working memory (direct digits: F=7.7, P=0.01; inverse digits: F=14.26, P=0.01) and attention (attention registration 1: F=10.23, P=0.01; attention registration 2: F=4.33, P=0.04) were improved, following the intervention. Conclusion: Computerized Training of working memory and attention can enhance the language skills in children with ADHD. This result confirmed the role of attention and working memory on language skills.